Complete laparoscopic ileal augmentation cystoplasty with modified ureteral reimplantation using an extra peritoneal approach for neurogenic bladder with vesicoureteral reflux in patient: a case report - Xing, Qingfei; He, Li; Jin, Peiyan; Tian, Dongxu; Wang, Ke; Guo, Feng (Frontiers in Surgery, 2025)
BackgroundNeurogenic bladder (NGB) is defined as bladder dysfunction. Patients with NGB often have issues with high-pressure storage of urine in the bladder and/or coordinated emptying of urine. Neurogenic bladders with high pressure may lead to vesicoureteral reflux (VUR).High-grade VUR leads to recurrent urinary tract infections (UTIs), and thus causes severe renal failure. Augmentation cystoplasty (AC) can reduce bladder pressure, increase bladder compliance, reduce vesicoureteral reflux, reduce the incidence of urinary incontinence, and improve the quality of life of patients. In recent years, with the maturity of laparoscopic technology, laparoscopic ileal augmentation cystoplasty has been widely used in clinical practice. However, through searching the database, we did not find any medical records of AC performed under complete laparoscopic via extraperitoneal approach. We report today a case of complete laparoscopic ileal augmentation cystoplasty with modified ureteral reimplantation using an extraperitoneal approach for neurogenic bladder with vesicoureteral reflux in a patient.Case presentationA 61-year-old women was hospitalized with symptoms of recurrent frequent urination. The patient had a urine volume of about 50 ml each time, no symptoms of dysuria, and no previous history of tuberculosis, diabetes and lumbar disc herniation. After admission, in addition to routine examinations, we also conducted abdominal CT, retrograde cystography, cystoscopy and urodynamic examination for the patient. Eventually, the patient was diagnosed with neurogenic bladder and bilateral ureteral reflux. The patient underwent a complete laparoscopic ileal augmentation cystoplasty with modified ureteral reimplantation using an extraperitoneal approach. Six months after the operation, the bladder volume expanded to 400 ml, and acute pyelonephritis did not occur. We ordered a CT scan of the patient, which showed no dilated ureter.ConclusionComplete laparoscopic ileal augmentation cystoplasty with modified ureteral reimplantation using an extraperitoneal approach is difcult due to the complex operation procedure and technical difculties. This investigation demonstrated that the extraperitoneal technique of enterocystoplasty that we describe is safe and feasible and has the advantages of less trauma, less bleeding, faster return of intestinal function, and fewer postoperative complications.